2005
DOI: 10.1007/bf02893034
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune thyroid disorders—An update

Abstract: Autoimmune thyroid disease (AITD), a common organ specific autoimmune disorder is seen mostly in women between 30-50 yrs of age. Thyroid autoimmunity can cause several forms of thyroiditis ranging from hypothyroidism (Hashimoto's thyroiditis) to hyperthyroidism (Graves'Disease). Prevalence rate of autoimmune mediated hypothyroidism is about 0.8 per 100 and 95% among them are women. Graves' disease is about one tenth as common as hypothyroidism and tends to occur more in younger individuals. Both these disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 37 publications
2
60
0
6
Order By: Relevance
“…In addition, Mohanty et al [16] showed that 45 of the 61 subclinical hypothyroid patients had elevated anti-TPO (73.78%), this finding also be in accord with our study. In agreement with our study Swain et al has also reported that most (95%) of the patients with autoimmune thyroid disease were women, mainly belonging to the age group of 30-50 years [2].…”
Section: Discussion:-supporting
confidence: 93%
See 1 more Smart Citation
“…In addition, Mohanty et al [16] showed that 45 of the 61 subclinical hypothyroid patients had elevated anti-TPO (73.78%), this finding also be in accord with our study. In agreement with our study Swain et al has also reported that most (95%) of the patients with autoimmune thyroid disease were women, mainly belonging to the age group of 30-50 years [2].…”
Section: Discussion:-supporting
confidence: 93%
“…An autoimmune thyroid disease (AITD) is by far the most frequent cause of Hypothyroidism and is characterized by the presence of antithyroid antibodies. Autoimmune thyroid diseases are common organ-specific autoimmune disorders mostly seen in women 30-50 years old [2]. It occurs due to loss of tolerance to autoantigens thyroid peroxidase (TPO), thyroglobulin (Tg), thyroid stimulating hormone receptor (TSH-R) which leads to the infiltration of the gland.…”
mentioning
confidence: 99%
“…Susceptibility to the diseases is determined by a combination of genetic, environmental, and endogenous factors [2].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-TPOAb reflects lymphocytic infiltration even in subclinical state of thyroid dysfuction. 2,4,5 The present study has evaluated anti-TPOAb level in patients with abnormal thyroid function test.…”
Section: Introductionmentioning
confidence: 99%